2015
DOI: 10.1111/bjd.13667
|View full text |Cite
|
Sign up to set email alerts
|

Typing ofPropionibacterium acnes: a review of methods and comparative analysis

Abstract: Propionibacterium acnes is a major commensal of the human skin. However, it is also the pathogen responsible for acne vulgaris and other diseases, such as medical-device infections. Strains of Propionibacterium acnes have long been classified into several different types. Recently, typing systems for this bacterium have taken on an increased importance as different types of P. acnes have been found to be associated with different disease states, including acne. Genetic approaches based on individual or multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…Many other phylotypes are of potential interest, since they have been recently shown to have differing disease associations, including for acne vulgaris [28, 29, 39]. We are currently characterizing the full proteome of several of these phylotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Many other phylotypes are of potential interest, since they have been recently shown to have differing disease associations, including for acne vulgaris [28, 29, 39]. We are currently characterizing the full proteome of several of these phylotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies found that certain phylotypes (IA‐2 with plasmid factor, IB‐1, I‐C) of C. acnes were more commonly associated with acne, while others (II‐ribotype 6, III) were exclusively associated with healthy skin . Therefore, these phylotypes may be a factor in the pathogenesis of acne.…”
Section: Methodsmentioning
confidence: 99%
“…An in vitro study revealed that acne‐associated phylotypes induce high T helper cell (Th)1 and Th17 responses, while healthy skin‐associated phylotypes induce relatively low Th1 and Th17 responses, but a high interleukin (IL)‐10 anti‐inflammatory response . This suggests that the healthy skin‐associated C. acnes phylotypes may be of use in a topical probiotic treatment or preventative regimen, designed to replace acne‐associated and other potentially opportunistic phylotypes . Such a targeted strategy utilizing the same species of bacteria that share an ecological niche may be a more effective approach than using other skin or especially gut commensals, by allowing faster and longer‐lasting improvements to the skin microbiota.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have experienced an explosion of sequence‐based typing methods for P. acnes . In this issue of the BJD Dr Yang Yu and coworkers present a timely review and comparison of these methods. Application of some of these methods may provide new insight into our complex relationship with P. acnes and pave the way for new prevention and treatment strategies.…”
mentioning
confidence: 99%